2011
DOI: 10.1074/jbc.m111.247650
|View full text |Cite
|
Sign up to set email alerts
|

Isopeptide Ligation Catalyzed by Quintessential Sortase A

Abstract: The housekeeping transpeptidase sortase A (SrtA) from Staphyloccocus aureus catalyzes the covalent anchoring of surface proteins to the cell wall by linking the threonyl carboxylate of the LPXTG recognition motif to the amino group of the pentaglycine cross-bridge of the peptidoglycan. SrtA-catalyzed ligation of an LPXTG containing polypeptide with an aminoglycine-terminated moiety occurs efficiently in vitro and has inspired the use of this enzyme as a synthetic tool in biological chemistry. Here we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Several groups have now optimized this reaction to modify proteins with a range of molecules, including drugs, lipids, sugars, fluorophores, and peptides 1321 . While Sa SrtA is potent tool, it is almost exclusively used to modify target proteins at their N- or C-termini, while it labels internal lysine side chains as a side reaction with low sequence specificity 15,22,23 . Here we show that a mutationally activated sortase enzyme from Corynebacterium diphtheriae ( Cd SrtA) can site-specifically install a peptide on a protein via a lysine-isopeptide bond.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have now optimized this reaction to modify proteins with a range of molecules, including drugs, lipids, sugars, fluorophores, and peptides 1321 . While Sa SrtA is potent tool, it is almost exclusively used to modify target proteins at their N- or C-termini, while it labels internal lysine side chains as a side reaction with low sequence specificity 15,22,23 . Here we show that a mutationally activated sortase enzyme from Corynebacterium diphtheriae ( Cd SrtA) can site-specifically install a peptide on a protein via a lysine-isopeptide bond.…”
mentioning
confidence: 99%
“…Transglutaminases can also modify protein lysine residues, but unlike Cd SrtA 3M , these enzymes exhibit minimal substrate specifity 35,36 . Similarly, Sa SrtA can modify lysines as a side reaction that occurs with minimal specificity and at low efficiency because the lysine ε-amine is not Sa SrtA’s natural substrate 15,22,23 . Chemical methods that modify amino acid side chains have also been developed, but they often require cysteine or non-natural amino acid incorporation into the protein and in some instances harsh reaction conditions 37 .…”
mentioning
confidence: 99%
“…Hydrolylsis of the intermediate, another typical side reaction, proceeds always more efficiently 111. 112 However, in the case of the corresponding cyclization even a transient intermediary acyl–enzyme complex can lead to intermolecular isopeptide bonds if the stereochemical positioning of the participating residues is favorable 112…”
Section: Optimizing Transpeptidationmentioning
confidence: 99%
“…31 Roy and co-workers found that SrtA could catalyze an “isopeptide” ligation, namely, transferring peptide substrates with a LPXTG motif to the ε–amino group of Lys residue to form cyclic and/or branched oligomers. 33 Recently, Guo and co-workers 34 applied SrtA to cyclic peptide and glycopeptide synthesis and identified the minimal size required for peptide head to tail cyclization. It was concluded that this method is applicable to the preparation of macrocyclic peptides and glycopeptides containing 15 or more amino acids.…”
Section: Srta–mediated Peptide/protein–peptide/protein Nucleic Acmentioning
confidence: 99%